Short-Run Welfare Impacts of Factory Jobs : Experimental Evidence from Ethiopia - Abebe, Girum; Buehren, Niklas; Goldstein, Markus (World Bank, Washington, DC, 2020)
Many countries in Sub-Saharan Africa face a rapidly growing population and labor force in demand of good jobs. Ethiopia has reacted to this challenge by prioritizing large-scale industrial development through the construction of industrial parks to drive exports, job creation, and growth. However, the African experience with industrial parks so far has been mixed. To provide further evidence on the welfare effects of factory jobs in Ethiopia, this study conducted an experiment that facilitated the job application and onboarding process for young female job seekers at three factories. Using panel data from 827 applicants, the study finds that the extra support increased the likelihood of being employed in the treatment group in the short run, largely driven by wage and factory work. Further, the intervention raised reported monthly income by nearly 30 percent in the treatment group. However, the study also finds an adverse impact on health outcomes as well as downward adjustments of applicants' expectations and perceptions of the earnings potential and desirability of factory work in response to the treatment.